Metabolic-hypoxic modulation of cytokine induction of intestinal endothelial adhesion molecules: Relevance to ischemic injury mediated necrotizing enterocolitis?. Issue 2 (June 2019) - Huda, Shehzad A.; Pramanik, Arun Kumar; Ganta, Vijay Chaitanya; Jennings, Merilyn; Alexander, Jonathan Steven
Abstract: Background: Necrotizing enterocolitis (NEC) triggers an intense inflammatory response in the neonatal gut associated with cytokine activation, altered nutrient status and intracellular O2 -deprivation. Endothelial cell adhesion molecules (ECAMs) play critical roles in driving immune cell infiltration into inflamed gut. Currently, relationships between inflammation, metabolism and ECAM expression remain poorly understood in NEC. We studied the effects of metabolic depletion (aglycemia/ hypoxia) on TNF-α mediated ECAM expression including ICAM-1, MAdCAM-1, VCAM-1 and E-selectin, in vitro in intestinal microvascular endothelial cells (IMEC). Methods: To study the effects of TNF-α, aglycemia and hypoxia (alone or in combination) IMECs expression of adhesion molecules was studied using cell surface ELISA and immunoblotting. Results: Total VCAM-1 expression was induced TNF-α and by hypoxia + TNF-α, cell surface expression was induced by hypoxia, TNF-α, TNF- α+hypoxia, and TNF- α+hypoxia and aglycemia. Total ICAM-1 increased following TNF- α, TNF- α+hypoxia, hypoxia + aglycemia, and TNF- α+hypoxia + aglycemia. Total MAdCAM-1 protein expression was significantly induced by a combination of TNF-α+hypoxia + aglycemia and cell surface expression induced by TNF- α+hypoxia. Surface expression of E-selectin was induced by TNF- α+aglycemia and TNF- α+hypoxia + aglycemia. Conclusion: Energy metabolism influences inflammation induced injury through mobilization of intestinal ECAMs, and may represent an important mechanism in NEC pathology.